A review of pollutant's interactions onto carbon nanotubes in wastewater treatment using density functional theory / Siti Umi Abd Rani and Marina Mokhtar - Abd Rani, Siti Umi; Mokhtar, Marina (2020)
Due to the abrupt developments in industrialization and urbanization, various pollutants especially heavy metals and organic pollutants are largely found in the wastewater system. The removal of the pollutants in aqueous solution by using carbon nanotubes as adsorbent has become a popular topic in research studies. However, the theoretical study regarding on determination of the interaction mechanism between carbon nanotubes and wastewater pollutants have never been reviewed. In this study, a review of interactions between pollutants in wastewater and carbon nanotubes using density functional theory method are provided. Two significant methods have been carried out in the study. Firstly, the relevant literature from online database is collected and filtered by using the following keywords: "quantum mechanics method" OR "density functional theory (DFT)" OR "interaction mechanism" AND "carbon nanotubes (CNTs)" AND "pollutants". Secondly, the useful content in selected literature was tabulated by extracting information based on some research questions. Based on the findings, the wastewater pollutants that studied using DFT consist of heavy metals such as zinc (II), mercury (II), lead (II) and chromium (VI) and organic pollutants likes phenols, reactive blue dye, methylene blue, acridine orange dye and anthracene. Whereas, the carbon nanotubes found in the DFT studies are pristine SWCNTs and functionalized SWCNTs likes carboxylic functionalized CNTs and amidoamine functionalized CNTs. The common interaction mechanism found between the carbon nanotubes and organic pollutants are van der Waals interaction, electrostatic interaction, ℼ- ℼ interaction and hydrogen bond. Meanwhile, the interaction found between carbon nanotubes and heavy metal are electrostatic attraction, coordination bond and complexation interaction. The DFT method that are widely used is B3LYP method and split valence with diffusion and polarization basis set such as 6-31+G and 6-31++G (d.p). From the findings, the DFT computational method is proven to be a great tool in providing the insight of the nature of the adsorption of wastewater pollutants onto carbon nanotubes.